Investigative competencies and teaching performance in a full-day educational institution, in an urban context, during the year 2019: a sequential exploratory analysis - Ticona Calizaya, Graciela Lourdes (2023)
The present study carries out a case study and exploratory sequential analysis around INVESTIGATIVE COMPETENCES and their interrelation with TEACHING PERFORMANCE in a full-time educational institution in the urban environment of the city of Tacna, during the year 2019. The investigative competence, which is included in the domains of information search, information technology, methodology and communication, is analyzed in its link with teaching performance, specifically in the promotion of reasoning, critical thinking and creativity, as well as in the evaluation of progress. of student learning and adaptation of pedagogical work. The research adopts a qualitative approach, in whose first phase cases of teacher performance at "sufficient", "outstanding" and "in process" levels were selected, considering the classroom observation rubric as an evaluation instrument, followed by in-depth interviews to each case of voluntary participants, and the data was supplemented by reviewing the scale files (professional resume). The results reveal a discernible relationship between investigative skills and teaching performance, thus contributing to the understanding of the influence of these skills on educational work.